Functional characterization of Mousterian tools from the Caucasus using comprehensive use-wear and residue analysis - E. V. Doronicheva; L. V. Golovanova; J. V. Kostina; S. A. Legkov; G. N. Poplevko; E. I. Revina; O. Y. Rusakova; V. B. Doronichev (Scientific Reports, 2022)
Abstract The authors discuss functional characterization of Mousterian tools on the basis of their use-wear and residue analysis of five lithic tools from Mezmaiskaya cave and Saradj-Chuko grotto in the North Caucasus. The results represent the first comprehensive use-wear and residue analysis carried out on Mousterian stone artefacts in the Caucasus. This study unequivocally confirms the use of bitumen for hafting stone tools in two different Middle Paleolithic cultural contexts defined in the Caucasus, Eastern Micoquian and Zagros Mousterian.